EMISI GAS FORMALDEHIDA DARI BEBERAPA TINGKAT KETEBALAN KAYU LAPIS - Suwandi Kliwon (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
In this paper the determination of formaldehyde gas emission from plywood is presented. Six samples were colected from several plywood factories in Indonesia two samples were made by the center for Forest Products Research and Development Laboratory in Bogor.The results showed that the amount of formaldehyde gas emission from plywood varies from 3.080 ppm (3.6 mm thick) to 9.933 ppm (for 18.0 mm thick)